Resource Management: A Geographical Perspective - Poudel, Krishna Prasad (The Third Pole: Journal of Geography Education, 2014)
Nature provides resources to human beings for their survival. A resource manager requires understanding the definition of resource and its changing paradigm, dynamism and approaches in a specific social, cultural, and geographical ground. This article is an attempt to explore differences of traditional definition of ‘natural resources’ to more dynamic discourse of ‘resources are not, but they become’. This essay is based on exploratory review of the available published materials. This paper contains introduction, conceptual ground, the shifting paradigm, dynamism in the resource definition, natural resource management vis-à-vis resource management, resources classification, the evolution of the field of resource management, and the approaches of the resource management. The body of the text is finally followed by the references cited. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11526 The Third Pole Vol. 11-12, 2012 page:21-28